Safety and immunogenicity of quadrivalent meningococcal polysaccharide vaccine (MPV ACYW135) compared with quadrivalent meningococcal conjugate vaccine (Menactra®) in Malian children - Samba O. Sow; Milagritos D. Tapia; Fadima Cheick Haidara; Fatoumata Diallo; Youssouf Traore; Awa Traoré; Mamoudou Kodio; Ray Borrow; Kelly Townsend-Payne; Lin Yuan; Shuyuan Yang; Lei Shi; et al. (Taylor & Francis Group, 2023)
Affordable, polyvalent meningococcal vaccines are needed for use in emergency reactive immunization campaigns. A phase IV randomized, observer-blind, controlled study compared the safety and immunogenicity of a quadrivalent meningococcal polysaccharide vaccine (MPV-4, MPV ACYW135) and quadrivalent meningococcal ACWY conjugate vaccine (MCV-4, Menactra®). Healthy, 2- to 10-year-old children in Bamako, Mali, were randomized 1:1 to receive one dose of MPV-4 or MCV-4. Safety outcomes were evaluated for 6 months post-immunization. Immunogenicity for all serogroups was assessed for non-inferiority between MPV-4 and MCV-4 30 days post immunization by serum bactericidal antibody assay using baby rabbit complement (rSBA). From December 2020 to July 2021, 260 healthy subjects were consented and randomized. At Day 30 post-immunization, the proportions of subjects with rSBA titers ≥ 128 for all serogroups in the MPV-4 group were non-inferior to those in MCV-4 group. The proportions of subjects with rSBA ≥ 4-fold increase and rSBA titers ≥ 8 for all serogroups were similar among vaccine groups (P > .05). Geometric Mean Titers and Geometric Mean Fold Increases for all serogroups in both vaccine groups were similar (P > .05). Few local and systemic post-immunization reactions of similar severity and duration were observed within 7 days and were similar in both groups (P > .05). All resolved without sequelae. Unsolicited adverse events were similar in both groups regarding relationship to study vaccine, severity and duration. No serious adverse events were reported during the study period. MPV ACYW135 showed a non-inferior immunogenicity profile and a comparable reactogenicity profile to MCV-4 in Malian children aged 2-10 years. Clinical Trial Registration: NCT04450498.